Revitalization of Railway Station in Situbondo Regency - Joko Budiwiyanto; Shela Rachim (Institut Seni Indonesia Surakarta, 2022)
The revitalization of the railway station in Situbondo Regency is an effort to revitalize the function of the station and commercial function as a maintenance measure of a cultural heritage building in Situbondo Regency. This design aims to renew Situbondo Railway Station with facilities following the Indonesian Railway Station Service Standards. The design method includes input, synthesis/analysis, and output. This design uses the theme